2022
DOI: 10.1177/17479541211067989
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing acute and daily load parameters in match situations – a comparison of classic and 3 × 3 basketball

Abstract: Purpose 3 × 3 is a variation of classic basketball (BB) that imposes new demands on both athletes and coaches. The objective of this study was to comprehensively describe similarities and differences in load structures between 3 × 3 and BB. Method Between January 2020 and July 2021, internal and external load parameters of 90 elite BB and 3 × 3 athletes were monitored during 84 games using a local positioning system (10 Hz) and inertial movement sensors (100 Hz). Results Male BB games last about 90 min; female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(54 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…When compared to the results obtained in the present investigation, it is interesting to note that 3×3 basketball players demonstrated somewhat poorer agility and better sprinting performance than 5×5 players examined in the aforementioned studies [ 4 , 27 ]. This may be attributed to the differences in testing methodologies (e.g., timing gates vs. stopwatch) and on-court playing demands between these two competitive styles as 3×3 basketball players are required to continuously perform high-speed inertial movements that ultimately result in a greater number of accelerations, decelerations, and distance covered at high-intensity thresholds [ 2 , 28 ]. In addition, the times to complete the shuttle run (i.e., formerly known as the suicide run) were faster for 3×3 basketball players examined in the present study when compared to collegiate elite and average-level 5×5 basketball players [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…When compared to the results obtained in the present investigation, it is interesting to note that 3×3 basketball players demonstrated somewhat poorer agility and better sprinting performance than 5×5 players examined in the aforementioned studies [ 4 , 27 ]. This may be attributed to the differences in testing methodologies (e.g., timing gates vs. stopwatch) and on-court playing demands between these two competitive styles as 3×3 basketball players are required to continuously perform high-speed inertial movements that ultimately result in a greater number of accelerations, decelerations, and distance covered at high-intensity thresholds [ 2 , 28 ]. In addition, the times to complete the shuttle run (i.e., formerly known as the suicide run) were faster for 3×3 basketball players examined in the present study when compared to collegiate elite and average-level 5×5 basketball players [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 3x3, Montgomery and Maloney (2018) reported that 17% of males' and 13% of females' total accelerations are highspeed movements, de ned as accelerations with more than 3.5 m*s − 1 . The number of decelerations exceeds the number of accelerations in moderate (> 2.5 m*s − 1 ) and high-speed movements in males and females 1,12 . Within a single 3x3 game, female athletes perform 33.53 (± 13.76) DEC and 32.75 (± 13.85), male athletes perform 44.16 (± 18) DEC and 33.92 (± 14.59) ACC.…”
mentioning
confidence: 84%
“…Another parameter that might affect the musculoskeletal system is the jump count since the athletes need to generate concentric force to lift off the ground and they need to resist eccentric forces during landing. Willberg et al (2022) reported 3x3 male athletes to perform 21.8 (± 8.5) jumps per game (1.7 per minute) and females to perform 16.6 (± 7.5) jumps per game (1.4 per minute) 12 .…”
mentioning
confidence: 99%
“…The authors reported that 17% of males’ and 13% of females' total ACC are high-speed movements, defined as ACC with more than 3.5 m*s −2 . The number of DEC exceeds the number of ACC in moderate (> 2.5 m*s −2 ) and high-speed movements in males and females [ 1 , 13 ]. Within a single 3 × 3 game, female athletes perform 33.53 (± 13.76) DEC and 32.75 ACC (± 13.85), while male athletes perform 44.16 (± 18) DEC and 33.92 (± 14.59) ACC.…”
Section: Introductionmentioning
confidence: 99%
“…On average, the jump count in male 3 × 3 games is 21.8 (± 8.5), with 1.7 jumps being performed per minute. Female jumps count is 16.6 (± 7.5) jumps per game, and 1.4 jumps are performed per minute [ 13 ].…”
Section: Introductionmentioning
confidence: 99%